THE PLASTIC STRESS ANALYSIS AT THE LAMINATED THERMOPLASTIC COMPOSITE PLATES WITH ELLIPTIC HOLE - Orcen, Gurbet; Gur, Mustafa; Solmaz, M. Yavuz (Gazi Univ, Fac Engineering Architecture, 2009)
In this paper, it is carried out the spread of plastic zones and the stress analysis at the composite plates with laminated thermoplastic ( Polyvinyl Chloride) subsisting an elliptic hole in the middle part. The composite plates with steel fiber reinforcement of woven-shaped consist of four orthotropic layers bonded symmetrically in the form of [theta(0)/theta(0)](2). The plates are subjected to uniformly distributed vertical loads. Loading is realized by iterations number of 25, 50, 75 and 100 by increments 0.0001 MPa by starting from the yielding point of plate for the chosen each reinforcement angle. According to the load steps and the different reinforcement angles, the values of the plastic stresses occurring in the composite plates are obtained by Finite Element Method. The obtained results present that the plastic zones in the plate appear in the lower and upper surfaces but not in the intermediate surfaces. It is also observed that the stress components at the intermediate layers are less than that of the lower and upper surfaces and the plastic stress components increase depending on the iteration number.
Keywords: Laminated composite materials; thermoplastics; plastic stress analysis; finite element method